Enhanced transportation of crude oil from the East Baghdad field using kerosene mixed with silica nanoparticles and the presence of surfactant - Khamees, Luay Ahmed; Abdul-Majeed, Ghassan H.; Alhaleem, Ayad A. (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
This study investigates the enhancement of heavy crude oil transportability from the East Baghdad Oil field through viscosity and density reduction. The proposed approach combined the use of silica (SiO₂) nanoparticles, kerosene, and the anionic surfactant SDBS. Prior to application, the silica nanoparticles were thoroughly characterized using thermogravimetric analysis (TGA), X-ray diffraction (XRD), atomic force microscopy (AFM), scanning electron microscopy (SEM), and energy-dispersive X-ray spectroscopy (SEM-EDX). These techniques confirmed the particles’ thermal stability, crystalline structure, nanoscale morphology, and elemental composition, validating their suitability for crude oil modification. A nanofluid was formulated with 18 vol% kerosene, 2 wt% SiO₂ nanoparticles, and 10wt% surfactant relative to nanoparticle mass. The mixture was dispersed ultrasonically under controlled thermal and temporal conditions. Optimal performance was achieved at 75 °C and 60 minutes of mixing, reducing viscosity from 58.15 cP to 16.53 cP and increasing API gravity from 19.67 to 28.84. Further enhancement was achieved with increased additive concentrations of 30% vol. kerosene, 3,000 ppm SiO₂, and 300 ppm surfactant, yielding a viscosity of 5.5 cP and an API gravity of 32.67. These results correspond to improvements of 90.5% and 66%, respectively. Control experiments using kerosene alone highlighted the superior efficiency of the ternary system. Given its affordability and availability, kerosene contributes to the practicality of this technique, offering a scalable and economically viable strategy for upgrading heavy crude oil in real-field applications.